THYROID ABSCESS IN CHILDREN: AND THE WORLD GETS STRANGER - Sarfaraz, Moaziz; Hasan, Syeda Rana; Qureshi, Zahid (Journal of Ayub Medical College Abbottabad, 2018)
The eminent feature of the thyroid gland in its resistance to infection by virtue of a rich blood supply and lymphatic drainage. Concomitantly, a high iodine content is also bactericidal. Acute suppurative thyroiditis, which leads to primary thyroid abscess, is an unusual type of head and neck infection. And above all, if it is in a paediatric age; it is quite rare. We have the opportunity to present such a noticeable case which was treated successfully by oral antibiotic therapy. Keywords: Thyroid abscess; Suppurative thyroiditis; Surgical management